High temperature fretting behaviour of plasma vapour deposition TiN coatings - Ramalho, A. (2002)
Fretting tests (mode I) were performed on TiN coatings at test temperatures of 23-500 °C. The evolution of the coefficient of friction with the number of fretting cycles for tests performed in that temperature range was recorded. Differences in that evolution were analysed based on the frictional energy dissipated in the sliding contact during the fretting tests. That analysis demonstrated the role of dissipated frictional energy and thermal energy in initiating a structural modification of the debris. The structural modification of the debris coincides with the transition from high friction conditions taking place in the presence of amorphous debris to low friction conditions in the presence of nano-crystalline debris.